Survey on the Use of Project Based Learning Model in Teaching Speaking at SMPN 2 Ayamaru - Binnendyk, Sophia; Bilmona, Hanafi; Lewier, Christian Albert; Hukom, Salmon; Hukom, Salmon (MATAI: International Journal of Language Education, 2024)
Project Based Learning (PBL) has implemented as a teaching model in English class. This study aims to explore teacher’s and students’ perception on the use of PBL in speaking class. The study used descriptive qualitative research. It was carried out at SMPN 2 Ayamaru, and the sample of the study is an English teacher and three students. In collecting the data, the researchers used interview. There were six questions for teacher and five questions for students. The results show that both teacher and students had positive impression about the use of PBL in speaking class. The teacher used PBL because its characteristics were appropriate with speaking as tool of communication. PBL can help students in improving their speaking ability, besides PBL also promotes team and collaborative work among students. In doing a project, the students can give feedback toward language barriers when their mates did mistakes. The teacher also can provide feedback. Lastly, the students feel more confident in presenting the project because in PBL, the students did more practice in groups.